THE DIVERSITY SPECIES OF THE ORDER TETRAODONTIFORMES FROM VIETNAM - Hoa, Tran Thi Hong; Phung, Nguyen Huu; Van, Tran Thi Le; Quang, Vo Van (Vietnam Journal of Marine Science and Technology, 2006)
THE DIVERSITY SPECIES OF THE ORDER TETRAODONTIFORMES FROM VIETNAM